2003
DOI: 10.1109/tec.2003.811746
|View full text |Cite
|
Sign up to set email alerts
|

IPM synchronous machine drive response to symmetrical and asymmetrical short circuit faults

Abstract: Abstract-A closed-form solution is presented for the steady-state response of interior permanent magnet (IPM) synchronous machines to symmetrical short circuits including the effects of -axis magnetic saturation. Machine response to single-phase asymmetrical short circuits is also investigated. Experimental data are presented to verify predicted behavior for both types of short circuits. It is shown that single-phase asymmetrical short circuit faults produce more severe fault responses with high pulsating torq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(72 citation statements)
references
References 13 publications
1
65
0
3
Order By: Relevance
“…The output current and power versus output voltage loci can be obtained by solving the interior PM machine's steady-state equations for a variable resistive load [9], [12]. Assuming a lossless, magnetically linear model, it can be shown that when these curves are normalized to the machine's short-circuit current and open-circuit voltage, their shape is not affected by speed and depend only on the machine's saliency ratio (see Fig.…”
Section: A Alternator Characteristics With Resistive Loadmentioning
confidence: 99%
See 2 more Smart Citations
“…The output current and power versus output voltage loci can be obtained by solving the interior PM machine's steady-state equations for a variable resistive load [9], [12]. Assuming a lossless, magnetically linear model, it can be shown that when these curves are normalized to the machine's short-circuit current and open-circuit voltage, their shape is not affected by speed and depend only on the machine's saliency ratio (see Fig.…”
Section: A Alternator Characteristics With Resistive Loadmentioning
confidence: 99%
“…The high-power alternator requirement is also indicated. now be calculated using the approach given in [13] for inverter operation and in [9], [10], and [12] for inverterless operation.…”
Section: B Normalization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the constant excitation provided from the permanent magnets in the rotor, the fault characteristics of permanent magnet motors differ from those of conventional induction motors. [15][16][17] A fault analysis was conducted in [18] to specify the severity of different faults in the electric driveline of an EV. Based on the results in [17][18][19][20][21], the following severe fault conditions were analysed, as these result in high changes in the torque characteristics: a three-phase balanced short circuit, an inverter shutdown, a single-transistor turn-on failure, 2 a current sensor misalignment and a controller fault.…”
Section: Fault Collection and Groupingmentioning
confidence: 99%
“…The steady-state UCG model is extended to take into account stator resistance and magnetic saturation and the model predictions are compared with experimental data taken from two IPM machines. A dynamic model [5] is used to predict transient waveforms and other transient effects present in the IPM machine during UCG operation.…”
Section: B Ucgmentioning
confidence: 99%